Teaching Mathematics Effectively to Primary Students in Developing Countries : Insights from Neuroscience and Psychology of Mathematics - Soendergaard, Bettina Dahl; Cachaper, Cecile (World Bank, Washington, DC, 2017)
This paper uses research from neuroscience and the psychology of mathematics to arrive at useful recommendations for teaching mathematics at primary level to poor students in developing countries. The enrollment rates of the poorer students have improved tremendously in the last decade. And the global Net Enrollment Ratio (NER) has improved since 2001 from 83.2 percent to 90-95 percent except in Sub-Saharan Africa and South Asia. Making teaching of math and other subjects efficient for the poor in developing countries is a great challenge, particularly in south Asia and Sub-Saharan Africa. Many developing countries have explored new means of teaching math and other subjects. Mongolia changed its mathematics education, aiming to build a new set of priorities and practices, given the abandonment of earlier traditions. Similar to international trends of the time, South Africa in the 1990s extensively applied the constructivist learning philosophy which relied on exploration and discovery, with little emphasis on memorization, drill, In conformity with a belief that teachers could develop their own learning programs, there was virtual absence of a national or provincial syllabus or textbooks. Students were expected to develop their own methods for arithmetic operations, but most found it impossible to progress on their own from counting to actual calculating. This study integrates pertinent research from neuroscience and the psychology of mathematics to arrive at recommendations for curricular and efficient means of mathematics instruction particularly for developing countries and poor students at primary level. Specifically, the latest research in neuroscience, cognitive science, and discussions of national benchmarks for primary school mathematics learning, form the basis of our recommendations. These recommendations have a reasonable chance of working in the situational contexts of developing countries, with their traditions and resources.